2020
DOI: 10.1111/obr.13086
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 in the pathophysiology of obesity and insulin resistance

Abstract: The association between plasma endothelin-1 (ET-1) and obesity has been documented for decades, yet the contribution of ET-1 to risk factors associated with obesity is not fully understood. In 1994, one of first papers to document this association also noted a positive correlation between plasma insulin and ET-1, suggesting a potential contribution of ET-1 to the development of insulin resistance. Both endogenous receptors for ET-1, ET A and ET B are present in all insulin-sensitive tissues including adipose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 83 publications
(213 reference statements)
0
16
1
1
Order By: Relevance
“…Insulin was initially believed to be a vasodilator because of its activation on NO secretion (30,31). However, in recent studies, insulin-induced vasodilation was confirmed to be impaired in insulin-resistant patients, and patients with obesity or insulin resistance have elevated ET-1 concentrations in the blood (32,33). The mechanism underlying the direct vascular effect of insulin on endothelial cells remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin was initially believed to be a vasodilator because of its activation on NO secretion (30,31). However, in recent studies, insulin-induced vasodilation was confirmed to be impaired in insulin-resistant patients, and patients with obesity or insulin resistance have elevated ET-1 concentrations in the blood (32,33). The mechanism underlying the direct vascular effect of insulin on endothelial cells remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…First, IR is correlated with endothelial dysfunction and atherosclerosis. IR is characterised by reduced phosphatidylinositol 3-kinase (PI3-K)/Akt pathway activity and increased expression of mitogen-activated protein kinase (MAPK) pathways; the disequilibrium between the two signals causes endothelial dysfunction, reduced nitric oxide (NO) production in endothelial cells, and increased endothelin-1 (ET-1) production, which may initiate oxidative stress, inflammatory cascade, and early stage atherosclerosis, [16][17][18][19] promote the development of CSVD, and accelerate cognitive impairment. Elevated levels of inflammatory cytokines are closely associated with IR.…”
Section: Discussionmentioning
confidence: 99%
“…ET-1 is the most potent vasoconstrictor substance identified, and it is widely distributed in cardiovascular and neural tissues, and the increased peripheral vascular resistance in essential hypertension may be related to its excessive production ( 10 ). NO is a gaseous biological messenger molecule that is widely involved in a variety of physiological and pathological processes in the body, and is considered to be a regulatory mediator in the regulation of vascular tone and maintenance of BP stability ( 11 , 12 ). The aim of this study was to investigate the relationship between the expression of serum ET-1 and NO levels and BP changes in patients with different degrees of BP in ESRD treated with HD after action endovenous fistula surgery and their correlation.…”
Section: Introductionmentioning
confidence: 99%